Paradigm shift in the microfinance sector and its implications for theory development: empirical evidence from Pakistan - Ashfaq A. Khan (Australasian Accounting, Business and Finance Journal, 2008)
Financial and non-financial subsidized resources at the disposal of international donor agencies available for continued support of the microfinance sector are not unlimited. One of the strategies resorted to by the donor community to ensure supply of financial resources to the sector was to make it lucrative to private-sector investment. Thus, for more than a decade now, the donor community has been emphasizing profitability on the part of microfinance institutions to enable the sector to attract commercial capital. This move on the part of the donor community led microfinance institutions to adapt both functionally and structurally to better cope with donor’s expectations and show them profits. Many microfinance institutions set example of successful adaptation and reorientation of their tangible and intangible organizational elements to enable them to survive under these new conditions. Laughlin’s (1991) Model of Organizational Change provides a theoretical base for understanding such an organizational change in the light of changing external circumstances. While the Model placated all the relevant research questions, it did not fully explain all the trends observed in the empirical data collected for the study, which lent a room for development in the Model.
Keywords: microfinance; organizational change; profitability; theory development; Pakistan.